Examining the Potential Impacts of Introducing a Cap and Share Scheme in Ireland - CAULFIELD, BRIAN (My University, 2011)
A cap and share scheme is a policy whereby a cap or limit is placed on national carbon dioxide (CO2) emissions and individuals are allocated an annual CO2 allowance. This paper examines some of the potential impacts of introducing a cap and share scheme in the transport sector in Ireland. The research presented in this paper focuses on travel-to-works trips specifically. CO2 emissions for these annual work trips are calculated and a cap is determined based on these results. Two caps are examined one based on average emissions and one set at a 20% reduction in average emissions as per Ireland’s reduction targets. A national and Dublin only cap are examined and the results are presented as a means of comparison. Binary logistic models are used to determine the socio-economic characteristics of individuals who fall above and below the cap. The results demonstrate the importance of car ownership, journey distance, mode choice and household composition in determining whether a commuter is above or below a cap. Many commuters who fall above the cap are likely drive to work over long distances, have dependent children in their household and own more than one car.
90th Annual Meeting of the Transportation Research Board
PUBLISHED
Washington D.C.
Keywords: Cap and share; Emissions reduction; Smart & Sustainable Planet